Alternaria macrocephalae sp. nov. (Ascomycota: Pleosporaceae) associated with Atractylodes macrocephala in China - Aung, Sein Lai Lai; Guo, Zhuan Jun; Huang, Jia Hui; Nwe, Zin Mar; Yu, Zhi He; Deng, Jian Xin (Phytotaxa, 2025)
The medicinal plant Atractylodes macrocephala Koidz. (AM) is a common herb in China. In this study, a novel species within the Alternaria genus was isolated from AM plants showing typical Alternaria symptoms in Hefeng County, Enshi Tujia and Miao Autonomous Prefecture of Hubei Province, China. Multi-locus phylogenetic analysis using concatenated sequences of the internal transcribed spacer of the rDNA region (ITS), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), Alternaria major allergen gene (Alt a 1), translation elongation factor 1 alpha (TEF1), and RNA polymerase second largest subunit (RPB2) genes provided further evidence supporting the placement in Alternaria sect. Porri. Although the newly isolated strains clustered closely with A. guilanica and A. dichondrae, analyses revealed that they belonged to a distinct lineage supporting the establishment of a new species. Based on conidial size, septa, beak morphology, and conidiophore appearance, the isolated strains were differentiated from A. guilanica and A. dichondrae. On the basis of those molecular and morphological characteristics, the fungus is identified as a new species named Alternaria macrocephale.